Colloid structure, window glass and vehicle
By using SCA glue, the edge part thickness is larger than the middle part, the problem of optical distortion during colloid connection is solved, and the uniform setting of window glass and high-quality transmission of optical signals are achieved.
Patent Information
- Application Number
- CN202310074447.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-20
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-01-20
AI Technical Summary
The prior art can easily lead to optical distortion when setting up a colloid to connect the amplicon and automotive glass, affecting the transmission quality of the optical signal.
A colloidal structure made of SCA glue has a thickness of the edge portion greater than that of the middle portion to avoid optical distortion caused by thinning of edge position during hot pressing bonding.
The colloidal structure is uniformly arranged after curing, avoiding optical distortion of the window glass and improving the transmission quality of optical signals.
Smart Images

Figure CN116218385B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of vehicles, and in particular to a colloid structure, a vehicle window glass and a vehicle. Background Art
[0002] The current automobile driving field is gradually developing towards assisted driving, automatic driving, and unmanned driving. In order to match the functions of detection equipment such as laser radar and infrared cameras, automobile glass needs to have a sufficiently high transmittance to optical signals. Setting an anti-reflection film on the inside of the window glass can reduce the reflection of the automobile glass to optical signals and improve the transmittance of the automobile glass to optical signals.
[0003] Generally, a substrate with an anti-reflection film (i.e., an anti-reflection film) is connected to the automobile glass through a colloid to improve the transmittance of the window glass to optical signals. However, the current colloid setting method is prone to cause optical distortion of the window glass, resulting in a loss in the transmission quality of the optical signal. Summary of the invention
[0004] The embodiments of the present application provide a colloid structure, a vehicle window glass and a vehicle, which can make the colloid connecting the anti-reflection film and the glass evenly arranged after curing, thereby avoiding optical distortion of the vehicle window glass.
[0005] In a first aspect, the present application provides a colloid structure, wherein the material of the colloid structure is SCA glue, the colloid structure comprises a middle part and an edge part, the edge part is connected to the periphery of the middle part, and the thickness of the edge part is greater than the thickness of the middle part.
[0006] At present, SCA glue has a certain fluidity during hot pressing. If the thickness of the colloid structure is set uniformly, the glue at the edge of the colloid structure is easy to overflow in a semi-fluid state, resulting in a thinner edge thickness of the colloid structure, resulting in uneven thickness of the glue layer after curing, and the window glass is prone to optical distortion, resulting in the transmission quality of the optical signal being affected. The present application sets the thickness of the edge of the colloid structure to be greater than the thickness of the middle part, thereby avoiding the situation where the edge of the colloid structure becomes thinner during the pressing stage, thereby causing optical distortion.
[0007] In a possible implementation manner, the thickness of the edge portion is uniformly set, and the thickness of the middle portion is uniformly set.
[0008] In a possible implementation manner, the thickness of the edge portion is between 160 μm and 260 μm, and the thickness of the middle portion is between 120 μm and 200 μm.
[0009] In a possible implementation manner, a ratio of the thickness of the middle portion to the thickness of the edge portion is between 0.5 and 0.9.
[0010] In a possible implementation manner, the edge portion includes a first sub-portion and a second sub-portion that are arranged opposite to each other along a first direction, the first direction is a width direction of the colloid structure, and the first sub-portion and the second sub-portion are respectively located on opposite sides of the middle portion;
[0011] The width of the first sub-portion in the first direction is a first width, the middle portion includes a first side and a second side arranged opposite to each other in the first direction, the distance between the midpoints of the first side and the second side is a second width, and the ratio of the first width to the second width is between 0.18 and 0.27; and / or,
[0012] The width of the second sub-portion in the first direction is the first width, the middle portion includes a first side and a second side arranged opposite to each other in the first direction, the distance between the midpoints of the first side and the second side is the second width, and the ratio of the first width to the second width is between 0.18 and 0.27.
[0013] In a possible implementation manner, the edge of the colloid structure points in a direction toward the center of the colloid structure, the thickness of the edge portion gradually decreases, and the thickness of the middle portion gradually decreases.
[0014] In a possible implementation manner, the maximum thickness of the edge portion is between 180 μm and 260 μm, and the minimum thickness of the middle portion is between 100 μm and 180 μm.
[0015] In a possible implementation manner, the ratio of the maximum thickness of the edge portion to the minimum thickness of the middle portion is between 0.4 and 0.7.
[0016] In a possible implementation, the colloid structure includes a glass bonding surface, the glass bonding surface is used to connect to the laminated glass, the glass bonding surface is connected between the edge of the edge portion and the center position of the middle portion, the angle between the glass bonding surface and a reference surface is between 8°-15°, the reference surface is parallel to the first direction and the second direction, and the second direction is the length direction of the colloid structure.
[0017] In a second aspect, the present application provides a vehicle window glass, comprising a laminated glass and an information collection area, wherein the laminated glass comprises an outer glass plate, an intermediate layer and an inner glass plate, wherein the intermediate layer is sandwiched between the outer glass plate and the inner glass plate, wherein the outer glass plate has a first surface and a second surface opposite to each other, wherein the second surface faces the intermediate layer, and wherein the inner glass plate has a third surface and a fourth surface opposite to each other, wherein the third surface faces the intermediate layer;
[0018] An anti-reflection sheet is provided on the fourth surface of the inner glass plate, and along the thickness direction of the laminated glass, the projection of the anti-reflection sheet on the information collection area covers the information collection area, the anti-reflection sheet includes an anti-reflection film and a substrate, the anti-reflection film is provided on the surface of the substrate, and the anti-reflection film is farther away from the laminated glass than the substrate, wherein the anti-reflection sheet is fixed to the fourth surface of the inner glass plate through an adhesive layer, the adhesive layer is made of the colloid structure as described above, and the thickness of the adhesive layer is uniformly set.
[0019] In a possible implementation manner, the transmittance of the laminated glass to light with a wavelength range of 800nm-1600nm is greater than 88%.
[0020] In a possible implementation manner, the transmittance of the adhesive layer to light with a wavelength of 800nm-1600nm is greater than 98%.
[0021] In a possible implementation manner, the refractive index of the adhesive layer for light with a wavelength of 800 nm-1600 nm is in the range of 1.46-1.49.
[0022] In a possible embodiment, the substrate includes a peripheral side surface, and a connecting surface and a coating surface that are relatively arranged, the connecting surface is connected to the fourth surface of the inner glass plate through the adhesive layer, the coating surface is connected to the anti-reflection film, the peripheral side surface is arranged around the connecting surface and the coating surface, and the angle between the connecting surface and the peripheral side surface is 90°.
[0023] In a possible implementation, measured from one side of the first surface, the a value of the Lab value of the visible light reflection color of the information collection area ranges from -3 to +3, and the b value ranges from -3 to +3.
[0024] In a third aspect, the present application provides a vehicle, comprising an optical sensor assembly, a vehicle body and a vehicle window glass as described above, wherein the vehicle window glass is connected to the vehicle body, the optical sensor assembly is connected to the inside of the vehicle body, and the optical signal of the optical sensor can pass through the vehicle window glass.
[0025] The beneficial effects of the present invention are:
[0026] The present application provides a colloid structure, the material of the colloid structure is SCA glue, the colloid structure includes a middle part and an edge part, the edge part is connected to the periphery of the middle part, and the thickness of the edge part is greater than the thickness of the middle part. The vehicle window glass of the present application includes laminated glass, an adhesive layer and an anti-reflection film, the anti-reflection film is fixed to the inner surface of the laminated glass by the adhesive layer, and the adhesive layer is made of the above-mentioned colloid structure. The technical solution of the present application can make the thickness of the adhesive layer formed by the colloid structure connecting the anti-reflection film and the laminated glass after hot pressing and curing to be uniformly set, so as to avoid optical distortion of the vehicle window glass. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solution of the present application, the drawings required for use in the implementation manner will be briefly introduced below. Obviously, the drawings described below are only some implementation manners of the present application. For ordinary technicians in this field, other drawings can be obtained like these drawings without paying any creative work.
[0028] Figure 1 is a schematic structural diagram of a vehicle provided in an embodiment of the present application;
[0029] Figure 2 yes Figure 1 A schematic cross-sectional view of a vehicle window glass shown;
[0030] Figure 3 yes Figure 1 A schematic diagram of the structure of the vehicle window glass shown;
[0031] Figure 4 yes Figure 1 Another structural schematic diagram of the vehicle window glass shown;
[0032] Figure 5 yes Figure 1 Another schematic cross-sectional view of the vehicle window glass shown;
[0033] Figure 6 yes Figure 1 Another cross-sectional schematic diagram of the vehicle window glass shown;
[0034] Figure 7 It is a schematic diagram of the structure of the anti-reflection film and the colloid structure of the present application;
[0035] Figure 8 It is a schematic diagram of the first possible structure of the colloid structure of the present application;
[0036] Fig. 9 yes Figure 8 A schematic structural diagram of a cross section of the colloidal structure shown;
[0037] Fig.10is a schematic structural diagram of an angled cross section of a second possible implementation of the colloid structure of the present application;
[0038] Fig.11 It is a schematic structural diagram of another cross-section angle of a second possible implementation of the colloid structure of the present application. DETAILED DESCRIPTION
[0039] For ease of understanding, the terms involved in the embodiments of the present application are first explained.
[0040] And / or: It is just a way to describe the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone.
[0041] Multiple: refers to two or more than two.
[0042] Connection: should be understood in a broad sense. For example, A and B are connected, which can be either direct or indirect through an intermediary.
[0043] The specific implementation of the present application will be clearly described below in conjunction with the accompanying drawings.
[0044] The current automobile driving field is gradually developing towards unmanned driving, automatic driving, and automatic assisted driving. In order to match the functions of detection equipment such as laser radar and infrared cameras, automobile glass needs to have a sufficiently high transmittance to optical signals. Setting an anti-reflection film on the inside of the window glass can reduce the reflection of the automobile glass to optical signals and improve the transmittance of the automobile glass to optical signals.
[0045] Generally, the substrate with anti-reflection film is connected to the car glass through colloid to improve the transmittance of the car window glass to optical signals. However, the current setting method of colloid easily causes optical distortion of the car window glass, resulting in the loss of transmission quality of optical signals.
[0046] Based on this, the embodiments of the present application provide a colloid structure, a vehicle window glass and a vehicle, which can make the colloid connecting the anti-reflection film and the glass evenly arranged after curing, thereby avoiding optical distortion of the vehicle window glass.
[0047] See also Figure 1 , Figure 11 is a schematic diagram of the structure of a vehicle 1000 provided in an embodiment of the present application. The vehicle 1000 includes an optical sensor assembly 100, a vehicle body 200 and a vehicle window glass 300. The vehicle window glass 300 is connected to the vehicle body 200, and the vehicle window glass 300 includes an information collection area 301. The optical sensor assembly 100 is arranged inside the vehicle body 200, and the transmission path of the optical signal of the optical sensor assembly 100 passes through the information collection area 301 of the vehicle window glass 300. Exemplarily, the optical signal may be an infrared signal, and the wavelength range of the optical signal may be between 800nm-1600nm (including the endpoint values 800nm and 1600nm).
[0048] Exemplarily, the optical sensor assembly 100 may include an optical sensor and / or a range finder (LiDAR) type sensor. The optical sensor assembly 100 includes but is not limited to a laser radar (LiDAR), a near infrared camera, etc. The present application does not impose any specific restrictions on the type of the optical sensor assembly 100.
[0049] It should be noted that this embodiment is described using the vehicle window glass 300 as the front windshield of the vehicle 1000, but in other embodiments, the vehicle window glass 300 can also be the side window glass, sunroof glass or rear windshield of the vehicle 1000, and this application does not specifically limit the usage scenario of the vehicle window glass 300.
[0050] See also Figure 2 , Figure 2 yes Figure 1 A schematic cross-sectional view of a vehicle window glass 300 is shown. The vehicle window glass 300 includes a laminated glass 310, an anti-reflection film 320, and an adhesive layer 330. The anti-reflection film 320 is connected to the laminated glass 310 through the adhesive layer 330, and along the thickness direction of the laminated glass 310, the projection of the anti-reflection film 320 on the information collection area 301 covers the information collection area 301.
[0051] The laminated glass 310 includes an outer surface 3103 and an inner surface 3104 that are arranged opposite to each other. The outer surface 3103 is the surface of the laminated glass 310 that faces the outside of the vehicle 1000. The inner surface 3104 is the surface of the laminated glass 310 that faces the inside of the vehicle 1000. The laminated glass 310 also includes an outer glass plate 311, an inner glass plate 313, and an intermediate layer 312 sandwiched between the outer glass plate 311 and the inner glass plate 313.
[0052] The outer glass plate 311 includes a first surface 3111 and a second surface 3112 that are arranged opposite to each other. The first surface 3111 is the surface of the outer glass plate 311 away from the middle layer 312, and the first surface 3111 is the outer surface 3103 of the laminated glass 310. The second surface 3112 is the surface of the outer glass plate 311 facing the middle layer 312. The inner glass plate 313 includes a third surface 3131 and a fourth surface 3132 that are arranged opposite to each other. The third surface 3131 is the surface of the inner glass plate 313 facing the middle layer 312, and the fourth surface 3132 is the surface of the inner glass plate 313 away from the middle layer 312, and the fourth surface 3132 of the inner glass plate 313 is the inner surface 3104 of the laminated glass 310.
[0053] It should be noted that the laminated glass 310 used as the front windshield is usually curved, but the shape of the laminated glass 310 is not limited to the shape described above. It can be any shape that meets the use requirements of the vehicle window glass 300. For example, the laminated glass 310 can also be a flat plate. The embodiments of the present application do not have strict requirements on the shape of the laminated glass 310.
[0054] Exemplarily, the outer glass plate 311 and the inner glass plate 313 can be made of transparent glass or tinted glass, such as tinted green glass, tinted gray glass, etc., but the visible light transmittance of the outer glass plate 311 and the inner glass plate 313 must be greater than or equal to 70%, preferably greater than or equal to 80%, or even greater than or equal to 90%. The outer glass plate 311 and / or the inner glass plate 313 have a transmittance of at least 91% in the wavelength range of 800-1600nm. The transmittance of the laminated glass 310 in the range of 800-1600nm is at least 88%. The material of the outer glass plate 311 and the inner glass plate 313 may include soda-lime-silica glass, borosilicate glass, or aluminosilicate glass, etc.
[0055] Exemplarily, the thickness G1 of the outer glass plate 311 is greater than or equal to the thickness G2 of the inner glass plate 313. Preferably, the thickness of the outer glass plate 311 is greater than the thickness of the inner glass plate 313. More preferably, the ratio of the thickness of the outer glass plate 311 to the thickness of the inner glass plate 313 is greater than 2.5. More preferably, the inner glass plate 313 is treated by a chemical tempering process. For example, the thickness of the outer glass plate 311 is at least 0.5 mm greater than the thickness of the inner glass plate 313. The use of a thinner inner glass plate 313 can form a laminated glass 310 with an asymmetric thickness. On the basis of reducing the total thickness of the laminated glass 310 to achieve lightweighting, the strength of the laminated glass 310 is improved to a certain extent, and the transmittance of the laminated glass 310 to optical signals can be further improved.
[0056] The middle layer 312 is used to connect the outer glass plate 311 and the inner glass plate 313 to improve the safety of the vehicle window glass 300 so that it meets the safety standards and regulatory requirements for window glass for the vehicle 1000. The material of the middle layer 312 can be polyvinyl butyral (PVB), polyethylene octene copolymer (POE), polyurethane (PU), ethylene vinyl acetate (EVA), thermoplastic polyurethane elastomer (TPU) or ionomer polymer film (SGP).
[0057] See also Figure 3 , Figure 3 yes Figure 1 A structural schematic diagram of a vehicle window glass 300 is shown. The width direction of the vehicle window glass 300 is a first direction, that is, Figure 3 The X-direction shown in FIG. 3 is the second direction, that is, Figure 3 The Y direction is shown. The thickness direction of the window glass 300 is Figure 1 and Figure 2 The laminated glass 310 may further include an ink layer 314 and a heat-insulating coating 315. The ink layer 314 may be disposed along the edge of the laminated glass 310 and avoid the information collection area 301 of the vehicle window glass 300. For example, the ink layer 314 may be disposed on the second surface 3112 of the outer glass plate 311, such as Figure 5 Alternatively, the ink layer 314 may be disposed on the fourth surface 3132 of the inner glass plate 313, as shown in FIG. Figure 6 The heat-insulating coating 315 may be provided on the second surface 3112 of the outer glass plate 311, as shown in FIG. Figure 6 Alternatively, the heat-insulating coating 315 may be provided on the third surface 3131 of the inner glass plate 313, as shown in FIG. Figure 5 And the heat-insulating coating 315 avoids the information collection area 301 of the vehicle window glass 300 .
[0058] The heat-insulating coating 315 is a functional metal layer, which includes multiple dielectric layers and one or more metal layers, each of which is located between two adjacent dielectric layers. In the present application, "multiple" refers to two or more. On the one hand, the dielectric layer has the function of protecting the metal layer to prevent the metal layer from being oxidized, and on the other hand, it can also adjust the optical properties, mechanical properties and reflection color of the window glass 300. The material of the metal layer can be a metal or metal alloy selected from at least one element of Ag, Au, Cu, Al, and Pt, and the material of the dielectric layer can be at least one of nitrides, oxides, and oxynitrides of metals and alloys thereof such as zinc Zn, Sn, Ti, Si, Al, Ni, Cr, Nb, Mg, Zr, Ga, Y, In, Sb, V, Ta, etc.
[0059] It is understandable that the information collection area 301 of the glass 310 is not provided with the ink layer 314 and the heat-insulating coating 315 to avoid the ink layer 314 and the heat-insulating coating 315 reflecting the optical signal of the optical sensor assembly 100 and ensure the transmission quality of the optical signal.
[0060] For example, Figure 3 The periphery of the information collection area 301 may be provided with an ink layer 314, and the information collection area 301 may be located in the middle of the upper end of the laminated glass 310. Alternatively, please refer to Figure 4 , Figure 4 yes Figure 1 Another structural schematic diagram of a vehicle window glass 300 is shown. The information collection area 301 can be spaced apart from the area of the laminated glass 310 provided with the ink layer 314, and a heat insulation coating 315 is provided on the periphery of the information collection area 301. The present application does not specifically limit the position of the information collection area 301, and only needs to meet the position requirements of the transmission path of the optical signal of the optical sensor assembly 100.
[0061] For a possible implementation, see Figure 5 , Figure 5 yes Figure 1 Another cross-sectional schematic diagram of a vehicle window glass 300 is shown. The ink layer 314 is disposed on the second surface 3112 of the outer glass plate 311 . The heat-insulating coating 315 is disposed on the third surface 3131 of the inner glass plate 313 .
[0062] For another possible implementation, see Figure 6 , Figure 6 yes Figure 1 Another cross-sectional schematic diagram of the vehicle window glass 300 is shown. Different from the above embodiment, the heat insulation coating 315 is disposed on the third surface 3131 of the inner glass plate 313 , and the ink layer 314 is disposed on the fourth surface 3132 of the inner glass plate 313 .
[0063] It is understandable that the ink layer 314 and the heat-insulating coating 315 only need to be disposed on different surfaces of the laminated glass 310 , and the present application does not limit the specific locations of the ink layer 314 and the heat-insulating coating 315 .
[0064] See also Figure 7 , Figure 7 yes Figure 2Schematic diagram of the structure of the anti-reflection sheet 320 and the adhesive layer 330. The anti-reflection sheet 320 is arranged on the inner surface 3104 of the laminated glass 310, that is, the anti-reflection sheet 320 is arranged on the fourth surface 3132 of the inner glass plate 313. The anti-reflection sheet 320 includes a substrate 321 and an anti-reflection film 322. The anti-reflection film 322 is arranged on the surface of the substrate 321, and the anti-reflection film 322 is farther away from the laminated glass 310 than the substrate 321. The substrate 321 includes a peripheral side surface 3210, and a connecting surface 3211 and a coating surface 3212 that are arranged oppositely. The connecting surface 3211 is connected to the fourth surface 3132 of the inner glass plate 313 through the adhesive layer 330, and the coating surface 3212 is connected to the anti-reflection film 322. The peripheral side surface 3210 is arranged around the connecting surface 3211 and the coating surface 3212.
[0065] The top angle and edge of one end of the substrate 321 where the connecting surface 3211 is located can be grinded at right angles. That is, the angle between the connecting surface 3211 and the peripheral side surface 3210 can be 90°. It can be understood that the right-angle grinding of the side where the connecting surface 3211 of the substrate 321 is located can prevent the edge area where the anti-reflection film 320 and the laminated glass 310 are attached from having a gap, thereby preventing dust, impurities and other pollutants from filling the edge slit, thereby preventing the aging resistance of the colloidal structure from being damaged and the aesthetics of the edge of the anti-reflection film 320 from being affected.
[0066] The end of the substrate 321 where the coating surface 3212 is located is subjected to rounded edge grinding. That is, the edge vertex of the coating surface 3212 can be a rounded corner 3213, and the coating surface 3212 can be connected to the peripheral side surface 3210 of the substrate 321 through the curved surface 3214. Since the coating surface 3212 of the substrate 321 is rounded and edged, the end away from the laminated glass 310 is relatively smooth, and it is not easy to be damaged by scratches from external objects.
[0067] In a possible implementation, the thickness of the substrate 321 is 0.3-1.5 mm. Exemplarily, the thickness of the substrate 321 can be 0.3 mm, 0.55 mm, 0.7 mm, 1.1 mm, 1.5 mm, etc., preferably 0.3 mm, 0.55 mm, 0.7 mm. The shape of the substrate 321 can also be circular, trapezoidal and other irregular shapes. The substrate 321 needs to be chemically toughened before use, which can effectively eliminate the edge stress of the substrate 321 and improve the overall mechanical strength and flexibility of the substrate 321, and prevent the anti-reflection film 320 from cracking during the process of bonding with the laminated glass 310 or the edge of the anti-reflection film 320 from optical distortion.
[0068] The anti-reflection film 322 is provided on the coating surface 3212 of the substrate 321. Exemplarily, the anti-reflection film 322 can be formed on the coating surface 3212 by magnetron sputtering coating. The thickness of the anti-reflection film 322 can be between 100nm-2000nm (including the endpoint values of 100nm and 2000nm). Preferably, the thickness of the anti-reflection film 322 can be between 200nm-1200nm (including the endpoint values of 200nm and 1200nm). More preferably, the thickness of the anti-reflection film 322 can be between 300nm-800nm (including the endpoint values of 300nm and 800nm).
[0069] The anti-reflection film 322 may be a natural light anti-reflection film in the infrared band (infrared light with a wavelength of 800-1600 nm) or a P-polarized light anti-reflection film.
[0070] In a possible implementation, the anti-reflection film 322 is an infrared band natural light anti-reflection film. At a vehicle installation angle of (63±3°AOI), the natural light transmittance of the vehicle window glass 300 equipped with the natural light anti-reflection film is increased by more than 8% compared with the natural light transmittance of the vehicle window glass 300 without the anti-reflection film 320. Preferably, the natural light transmittance of the vehicle window glass 300 equipped with the natural light anti-reflection film is increased by more than 10% compared with the natural light transmittance of the vehicle window glass 300 without the anti-reflection film 320. More preferably, the natural light transmittance of the vehicle window glass 300 equipped with the natural light anti-reflection film is increased by more than 12% compared with the natural light transmittance of the vehicle window glass 300 without the anti-reflection film 320.
[0071] In another possible embodiment, the anti-reflection film 322 is an infrared band P-polarized light anti-reflection film. At the vehicle installation angle of (63±3°AOI), the P-polarized light transmittance of the vehicle window glass 300 equipped with the P-polarized light anti-reflection film is increased by more than 1.4% compared with the P-polarized light transmittance of the vehicle window glass 300 without the anti-reflection film 320. Preferably, the P-polarized light transmittance of the vehicle window glass 300 equipped with the P-polarized light anti-reflection film is increased by more than 1.5% compared with the P-polarized light transmittance of the vehicle window glass 300 without the anti-reflection film 320. More preferably, the P-polarized light transmittance of the vehicle window glass 300 equipped with the P-polarized light anti-reflection film is increased by more than 1.6% compared with the P-polarized light transmittance of the vehicle window glass 300 without the anti-reflection film 320.
[0072] The information collection area 301 provided with the anti-reflection film 320 is subjected to a color test, and the visible light reflection color of the information collection area 301 provided with the anti-reflection film 320 in the vehicle window glass 300 is measured from the side of the first surface 3111 (i.e., the outer surface 3103 of the laminated glass 310). The a value in the Lab value of the visible light reflection color ranges from -3 to +3 (including the endpoint values -3 and +3), and the b value ranges from -3 to +3 (including -3 and +3). The color of the information collection area 301 provided with the anti-reflection film 320 in the vehicle window glass 300 is achieved to be a neutral color when observed from the outside of the vehicle, so that the vehicle window glass 300 can maintain a good appearance when viewed from outside the vehicle.
[0073] Please refer to Figure 2 The adhesive layer 330 is disposed between the fourth surface 3132 of the inner glass plate 313 and the substrate 321. The adhesive layer 330 is made of the following colloid structure. The colloid structure in this application is referred to as Figures 8 to 11 The material of the colloid structure provided in the present application is SCA glue, and the colloid structure includes a middle portion 331 and an edge portion 332 . The edge portion 332 is connected to the periphery of the middle portion 331 , and the thickness of the edge portion 332 is greater than the thickness of the middle portion 331 .
[0074] It should be noted that the shapes of the adhesive layer 330 and the colloid structure are different before and after the lamination of the vehicle window glass 300. Specifically, before the laminated glass 310, the colloid structure and the anti-reflection film 320 are laminated, the thickness of the colloid structure is uneven, as described below. After the laminated glass 310, the colloid structure and the anti-reflection film 320 are laminated, the colloid structure is laminated and cured to form the adhesive layer 330, and the thickness of the adhesive layer 330 is uniformly set, so the adhesive layer 330 can stably transmit optical signals.
[0075] SCA glue (Solid Optically Clear Adhesive) is a solid UV type optical glue with excellent light transmittance and good bonding performance after curing. The bonding property of SCA glue before lamination is relatively small, and it is easier to rework, which greatly controls the occurrence of defective rate. When preparing the vehicle window glass 300, the present application uses the colloidal structure of the SCA glue material to paste the laminated glass 310 and the anti-reflection film 320, which is easy to rework before ultraviolet curing, thereby improving work efficiency and yield rate. In addition, SCA glue not only has a low production cost, but also is not prone to defects such as bubbles during the bonding process, which avoids the optical distortion area around the bubbles affecting the transmission of optical signals.
[0076] In actual production, the anti-reflection film 320 requires a temperature of more than 80°C during the SCA glue lamination stage. For example, the temperature required for the lamination stage can be between 80°C and 90°C. High temperature will cause the SCA glue to be in a semi-fluid state during hot pressing. Before lamination, if the thickness of the colloid structure made of SCA glue is set uniformly, then during the hot pressing process, the glue at the edge of the colloid structure is easy to overflow in a semi-fluid state, resulting in a thinner edge thickness of the colloid structure after lamination, resulting in uneven thickness of the cured colloid structure (i.e., the adhesive layer 330), causing optical distortion of the window glass, affecting the transmission quality of the optical signal and preventing the optical sensor assembly 100 from working properly. When the optical sensor assembly 100 inside the vehicle 1000 is working normally, it is required that the value of the light distortion generated by the information collection area 301 of the window glass 300 is less than or equal to 150mdpt.
[0077] The present application sets the thickness of the edge portion 332 of the colloid structure to be greater than the thickness of the middle portion 331, thereby avoiding the situation where the edge position of the colloid structure becomes thinner during the lamination stage, thereby causing optical distortion. Therefore, the present application can set the thickness of the adhesive layer 330 formed by the colloid structure connecting the anti-reflection film 320 and the laminated glass 310 after curing to be uniform, thereby avoiding the situation where the window glass 300 has optical distortion.
[0078] Please refer to Figure 8 , Figure 8 yes Figure 2 A possible structural diagram of a colloid structure is shown. The colloid structure includes a middle portion 331 and an edge portion 332. The edge portion 332 is connected to the periphery of the middle portion 331. Figure 7 , the colloid structure further includes a first bonding surface 333 and a second bonding surface 334 which are arranged opposite to each other in the Z direction. In actual use, the first bonding surface 333 is first connected to the connection surface 3211 of the substrate 321 in the anti-reflection film 320, and then the second bonding surface 334 of the colloid structure is aligned and connected to the inner surface 3104 of the laminated glass 310 (i.e., the fourth surface 3132 of the inner glass plate 313). Since the first bonding surface 333 is first bonded to the anti-reflection film 320 in actual use, the first bonding surface 333 can be set to a plane, so as to be directly bonded to the anti-reflection film 320. The second bonding surface 334 can be a concave surface, so that the thickness of the edge portion 332 of the colloid structure is greater than the thickness of the middle portion 331. The specific structure of the colloid structure is illustrated by the following embodiments.
[0079] The present application provides two ways of setting the colloid structure, in which the thickness of the edge portion 332 of the colloid structure is set to be greater than the thickness of the middle portion 331 of the colloid structure, thereby avoiding the situation in which the edge position 3301 of the colloid structure becomes thinner during the pressing stage, thereby causing optical distortion.
[0080] In the first possible implementation, please refer to Figure 8 and Fig. 9 , Fig. 9 yes Figure 8 The schematic diagram of the cross-section of the colloid structure shown in FIG. One side of the middle portion 331 is flush with the edge portion 332 in the Z direction, that is, the first bonding surface 333 is a plane. The other side of the middle portion 331 is concave relative to the edge portion 332 in the Z direction, that is, the second bonding surface 334 is a concave surface.
[0081] The thickness H1 of the middle portion 331 is uniformly set. The thickness H1 of the middle portion 331 may be between 120 μm and 200 μm (including the endpoint values 120 μm and 200 μm). Exemplarily, the thickness H1 of the middle portion 331 may be 120 μm, 160 μm, or 200 μm. The thickness H2 of the edge portion 332 is uniformly set. The thickness H2 of the edge portion 332 may be between 160 μm and 260 μm (including the endpoint values 160 μm and 260 μm). Exemplarily, the thickness H2 of the edge portion 332 may be 160 μm, 200 μm, 240 μm, or 260 μm. The thickness H2 of the edge portion 332 is greater than the thickness H1 of the middle portion 331. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 may be between 0.5 and 0.9 (including the endpoint values 0.5 and 0.9). Preferably, the ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 may be between 0.6 and 0.8 (including endpoint values 0.6 and 0.8).
[0082] The ratio of the width of the edge portion 332 (the first width D1 or the third width D2 described below) to the width of the middle portion 331 in the same direction (the second width W1 or the fourth width W2 described below) can be between 0.18 and 0.27 (including the endpoint values 0.18 and 0.27). The width of the edge portion 332 is the distance between the edge position of the colloid structure and the middle portion 331 in the X direction or the Y direction. The width of the middle portion 331 is the distance between the midpoints of the two opposite sides of the middle portion 331 in the X direction or the Y direction.
[0083] Specifically, the edge portion 332 includes a first sub-portion 3321 and a second sub-portion 3322 sequentially arranged along the X direction, and a third sub-portion 3323 and a fourth sub-portion 3324 sequentially arranged along the Y direction. The first sub-portion 3321 and the second sub-portion 3322 are respectively located on opposite sides of the middle portion 331 in the X direction. The third sub-portion 3323 and the fourth sub-portion 3324 are respectively located on opposite sides of the middle portion 331 in the Y direction.
[0084] For example, Figure 8 , the width of the first sub-portion 3321 is the distance between the edge of the colloid structure and the edge of the middle portion 331 in the X direction. The middle portion 331 includes a first side 3311 and a second side 3312 arranged opposite to each other in the X direction, and a third side 3313 and a fourth side 3314 arranged opposite to each other in the Y direction. The width of the middle portion 331 in the X direction is the distance between the midpoint of the first side 3311 and the midpoint of the second side 3312. Exemplarily, the shape of the colloid structure may be a trapezoid, and the shape of the middle portion 331 may be a trapezoid. At this time, the width of the middle portion 331 is half of the sum of the length of the third side 3313 and the length of the fourth side 3314.
[0085] The width of the first sub-portion 3321 in the X direction is a first width D1, and the width of the middle portion 331 in the X direction is a second width W1. The ratio of the first width D1 to the second width W1 may be between 0.18 and 0.27 (including endpoint values 0.18 and 0.27).
[0086] The width of the second sub-portion 3322 in the X direction may be the same as the width of the first sub-portion 3321 in the X direction, and the shape of the second sub-portion 3322 may be mirror-symmetrical to the shape of the first sub-portion 3321. The width of the second sub-portion 3322 in the X direction is the first width D1. And the ratio of the first width D1 of the second sub-portion 3322 to the second width W1 of the middle portion 331 may be between 0.18 and 0.27 (including the endpoint values 0.18 and 0.27).
[0087] The width of the third sub-portion 3323 in the Y direction may be a third width D2, and the width of the middle portion 331 in the Y direction may be a fourth width W2, which is also the distance between the midpoint of the third side 3313 and the midpoint of the fourth side 3314. The ratio of the third width D2 to the fourth width W2 may be between 0.18 and 0.27 (including the endpoint values 0.18 and 0.27).
[0088] The width of the fourth sub-portion 3324 in the Y direction may be the same as the width of the third sub-portion 3323 in the Y direction. The width of the fourth sub-portion 3324 in the Y direction is the third width D2. And the ratio of the third width D2 of the fourth sub-portion 3324 to the fourth width W2 of the middle portion 331 may be between 0.18 and 0.27 (including the endpoint values 0.18 and 0.27).
[0089] It should be noted that the shape of the above-mentioned colloid structure is only for schematic illustration. In actual use, the specific shape of the colloid structure can be set according to the shape of the anti-reflection film 320.
[0090] In the present application, the transmittance of the adhesive layer 330 to the light with a wavelength of 800nm-1600nm can be greater than or equal to 98%. The refractive index range of the adhesive layer 330 to the light with a wavelength of 800nm-1600nm is between 1.46-1.49 (including the endpoint values 1.47 and 1.49). Specifically, since the incident light will lose part of the light due to the reflection phenomenon due to the difference in refractive index between the media when penetrating the interface of the medium, when the light passes through the interface between the fourth surface 3132 of the inner glass plate 313 and the adhesive layer 330, for the near-infrared band with a wavelength of 800-1600nm, the refractive index of the adhesive layer 330 is 1.46-1.49, and the refractive index of the inner glass plate 313 is 1.43-1.47. Since the refractive index difference between the adhesive layer 330 and the inner glass plate 313 for the near-infrared band is very small, very little light is reflected at the interface of the medium, and at this time, the reflection loss of the light is very small, and the light transmittance is high. When light passes through the interface between the anti-reflection film 322 and the outside of the vehicle window glass, the anti-reflection film 322 is an anti-reflection film with an alternating structure of high and low refractive index film layers, and has a high transmittance in the near-infrared band with a wavelength of 800-1600nm; under the combined influence of the anti-reflection film 322 and the bonding layer 330, the transmittance of the vehicle window glass 300 in the near-infrared band with a wavelength of 800-1600nm is improved.
[0091] Exemplarily, the thickness of the adhesive layer 330 may be between 100 μm and 300 μm (including the endpoint values of 100 μm and 300 μm), and exemplary, the thickness of the adhesive layer 330 may be 120 μm, 160 μm, 200 μm, 240 μm, or 280 μm. Preferably, the thickness of the adhesive layer 330 may be between 150 μm and 250 μm (including the endpoint values of 150 μm and 250 μm). More preferably, the thickness of the adhesive layer 330 may be 160 μm, 200 μm, or 240 μm.
[0092] It is understandable that if the thickness of the adhesive layer 330 is too high, the anti-reflection film 320 will be more protruding relative to the inner surface 3104, making the window glass 300 unsightly and also affecting the transmittance of the optical signal. If the thickness of the adhesive layer 330 is too thin, it will not be able to play a buffering role between the laminated glass 310 and the anti-reflection film 320, resulting in the anti-reflection film 320 being broken due to the difference in the curvature of the anti-reflection film 320 and the laminated glass 310 during the bonding process. The thickness of the adhesive layer 330 of the present application can also play a sufficient buffering role between the laminated glass 310 and the anti-reflection film 320 without affecting the aesthetics of the window glass 300.
[0093] Exemplarily, the anti-reflection film 320 and the laminated glass 310 may be bonded together using the following process.
[0094] In the first step, the SCA glue is cut into corresponding sizes, the light film of the SCA glue is torn off, and the SCA glue of corresponding sizes is attached to the connection surface 3211 of the substrate 321. Specifically, the thinner SCA glue of the middle part 331 is first attached to the middle area of the connection surface 3211 of the anti-reflection film 320, and then the thicker SCA glue of the edge part 332 is attached to the edge area of the connection surface 3211 of the anti-reflection film 320, and then the surface film on the side of the glue structure away from the connection surface 3211 is torn off.
[0095] In the second step, a robotic arm is used to stick the anti-reflection film 320 to the information collection area 301 of the laminated glass 310 accordingly, and the anti-reflection film 320 and the laminated glass 310 are placed in a laminating machine for hot pressing lamination under a vacuum environment. The temperature in the chamber of the laminating machine ranges from 80°C to 90°C (including the endpoint values of 80°C and 90°C).
[0096] It should be noted that the laminating machine used is a specially customized laminating machine with a curvature matching the front windshield of the vehicle 1000. A mechanical automatic laminating process is adopted, and the lower bracket in the laminating machine matches the corresponding profile and curvature of the front windshield. The laminating machine uses a laminating airbag and a coating surface 3212 of the anti-reflection film 320 to perform progressive lamination extending from the center to the periphery, which ensures that the bubbles of the anti-reflection film 320 can be pressed out from the center to the periphery during the laminating process, and the force is evenly applied, thereby avoiding the problem of glass fragments and the problem of bubbles being unable to be discharged.
[0097] The third step is to put the bonded finished glass into a degassing machine. The parameters of the degassing machine are: the operating temperature range is between 65℃-75℃ (including the endpoint values 65℃ and 75℃), the operating pressure range is between 0.4MPa-0.6MPa (including the endpoint values 0.4MPa and 0.6MPa), and the degassing time is 30-40 minutes.
[0098] The fourth step is to put the finished glass into the UV curing machine with a curing energy of 5000MJ / cm 2 -6000MJ / cm 2 about.
[0099] The present application also provides four embodiment groups and four comparative example groups, wherein the ratio of the first width D1 to the second width W1 of the colloid structure of the four embodiment groups is between 0.18 and 0.27 (including the endpoint values 0.18 and 0.27). Each embodiment group includes four embodiments, and the ratio of the thickness H1 of the middle part 331 to the thickness H2 of the edge part 332 of each embodiment is different. In the four comparative example groups, the thickness of the colloid structure of one comparative example group is uniformly set, and the comparative example group includes four comparative examples, and the thickness of the colloid structure of each comparative example is different; the other three comparative example groups also include four comparative examples, and the ratio of the thickness H1 of the middle part 331 to the thickness H2 of the edge part 332 of each comparative example is different.
[0100] Specifically, the ratio of the first width D1 to the second width W1 of the colloidal structure of the first embodiment group is 0.18. The first embodiment group includes four embodiments, namely, embodiment 1, embodiment 2, embodiment 3 and embodiment 4.
[0101] The thickness H1 of the middle portion 331 of Example 1 is 160 μm, and the thickness H2 of the edge portion 332 is 200 μm. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 is 0.8.
[0102] The thickness H1 of the middle portion 331 of Example 2 is 120 μm, and the thickness H2 of the edge portion 332 is 200 μm. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 is 0.6.
[0103] The thickness H1 of the middle portion 331 of Example 3 is 160 μm, and the thickness H2 of the edge portion 332 is 240 μm. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 is 0.666.
[0104] The thickness H1 of the middle portion 331 of Example 4 is 120 μm, and the thickness H2 of the edge portion 332 is 240 μm. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 is 0.5.
[0105] The ratio of the first width D1 to the second width W1 of the colloidal structure of the second embodiment group is 0.2. The second embodiment group includes four embodiments, namely, embodiment 5, embodiment 6, embodiment 7 and embodiment 8.
[0106] The thickness H1 of the middle portion 331 of Example 5 is 160 μm, and the thickness H2 of the edge portion 332 is 200 μm. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 is 0.8.
[0107] The thickness H1 of the middle portion 331 of Example 6 is 120 μm, and the thickness H2 of the edge portion 332 is 200 μm. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 is 0.6.
[0108] The thickness H1 of the middle portion 331 of Example 7 is 160 μm, and the thickness H2 of the edge portion 332 is 240 μm. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 is 0.666.
[0109] The thickness H1 of the middle portion 331 of Example 8 is 120 μm, and the thickness H2 of the edge portion 332 is 240 μm. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 is 0.5.
[0110] The ratio of the first width D1 to the second width W1 of the colloidal structure of the third embodiment group is 0.25. The third embodiment group includes four embodiments, namely, embodiment 9, embodiment 10, embodiment 11 and embodiment 12.
[0111] The thickness H1 of the middle portion 331 of Example 9 is 160 μm, and the thickness H2 of the edge portion 332 is 200 μm. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 is 0.8.
[0112] The thickness H1 of the middle portion 331 of Example 10 is 120 μm, and the thickness H2 of the edge portion 332 is 200 μm. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 is 0.6.
[0113] The thickness H1 of the middle portion 331 of Example 11 is 160 μm, and the thickness H2 of the edge portion 332 is 240 μm. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 is 0.666.
[0114] The thickness H1 of the middle portion 331 of Example 12 is 120 μm, and the thickness H2 of the edge portion 332 is 240 μm. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 is 0.5.
[0115] The ratio of the first width D1 to the second width W1 of the colloidal structure of the fourth embodiment group is 0.27. The fourth embodiment group includes four embodiments, namely, embodiment 13, embodiment 14, embodiment 15 and embodiment 16.
[0116] The thickness H1 of the middle portion 331 of Example 13 is 160 μm, and the thickness H2 of the edge portion 332 is 200 μm. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 is 0.8.
[0117] The thickness H1 of the middle portion 331 of Example 14 is 120 μm, and the thickness H2 of the edge portion 332 is 200 μm. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 is 0.6.
[0118] The thickness H1 of the middle portion 331 of Example 15 is 160 μm, and the thickness H2 of the edge portion 332 is 240 μm. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 is 0.666.
[0119] The thickness H1 of the middle portion 331 of Example 16 is 120 μm, and the thickness H2 of the edge portion 332 is 240 μm. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 is 0.5.
[0120] Specifically, the ratio of the first width D1 to the second width W1 of the colloidal structure of the first comparative example group is 0.1. The first comparative example group includes four comparative examples, namely comparative example 1, comparative example 2, comparative example 3 and comparative example 4.
[0121] The thickness H1 of the middle portion 331 of Comparative Example 1 was 160 μm, and the thickness H2 of the edge portion 332 was 200 μm. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 was 0.8.
[0122] The thickness H1 of the middle portion 331 of Comparative Example 2 was 120 μm, and the thickness H2 of the edge portion 332 was 200 μm. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 was 0.6.
[0123] The thickness H1 of the middle portion 331 of Comparative Example 3 is 160 μm, and the thickness H2 of the edge portion 332 is 240 μm. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 is 0.666.
[0124] The thickness H1 of the middle portion 331 of Comparative Example 4 was 120 μm, and the thickness H2 of the edge portion 332 was 240 μm. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 was 0.5.
[0125] The ratio of the first width D1 to the second width W1 of the colloidal structure of the second comparative example group is 0.15. The second comparative example group includes four comparative examples, namely, comparative example 5, comparative example 6, comparative example 7 and comparative example 8.
[0126] The thickness H1 of the middle portion 331 of Comparative Example 5 was 160 μm, and the thickness H2 of the edge portion 332 was 200 μm. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 was 0.8.
[0127] The thickness H1 of the middle portion 331 of Comparative Example 6 was 120 μm, and the thickness H2 of the edge portion 332 was 200 μm. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 was 0.6.
[0128] The thickness H1 of the middle portion 331 of Comparative Example 7 is 160 μm, and the thickness H2 of the edge portion 332 is 240 μm. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 is 0.666.
[0129] The thickness H1 of the middle portion 331 of Comparative Example 8 was 120 μm, and the thickness H2 of the edge portion 332 was 240 μm. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 was 0.5.
[0130] The ratio of the first width D1 to the second width W1 of the colloidal structure of the third comparative example group is 0.3. The third comparative example group includes four embodiments, namely comparative example 9, comparative example 10, comparative example 11 and comparative example 12.
[0131] The thickness H1 of the middle portion 331 of Comparative Example 9 is 160 μm, and the thickness H2 of the edge portion 332 is 200 μm. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 is 0.8.
[0132] The thickness H1 of the middle portion 331 of Comparative Example 10 was 120 μm, and the thickness H2 of the edge portion 332 was 200 μm. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 was 0.6.
[0133] The thickness H1 of the middle portion 331 of Comparative Example 11 was 160 μm, and the thickness H2 of the edge portion 332 was 240 μm. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 was 0.666.
[0134] The thickness H1 of the middle portion 331 of Comparative Example 12 was 120 μm, and the thickness H2 of the edge portion 332 was 240 μm. The ratio of the thickness H1 of the middle portion 331 to the thickness H2 of the edge portion 332 was 0.5.
[0135] The thickness of the colloidal structure of the fourth comparative example group is uniformly set, and the fourth comparative example group includes four comparative examples, namely comparative example 13, comparative example 14, comparative example 15 and comparative example 16. Among them, the thickness of the adhesive layer formed after the colloidal structure of comparative example 13 is cured is 120 μm. The thickness of the adhesive layer formed after the colloidal structure of comparative example 14 is cured is 160 μm. The thickness of the adhesive layer formed after the colloidal structure of comparative example 15 is cured is 200 μm. The thickness of the adhesive layer formed after the colloidal structure of comparative example 16 is cured is 240 μm.
[0136] The above embodiments and comparative examples were subjected to optical performance tests and adhesion tests. The optical performance test was performed using a moiré scanner to test the optical distortion of the experimental object. The optical distortion was measured according to the optical power, which was expressed in milli-diopters (mpdt).
[0137] The bonding strength of the experimental object is tested using a tensile testing machine. The sample is clamped symmetrically on the fixture, and the distance from the clamp to the nearest bonding end is uniformly 50mm. The tensile testing machine tests at a constant test speed and records the maximum load of the sample shear failure as the failure load. If the maximum load is greater than 210N / 25mm, it means that the bonding strength meets the use requirements.
[0138] Table 1, test results of multiple examples and multiple comparative examples of the first possible implementation of the colloidal structure
[0139]
[0140]
[0141] The following conclusions can be drawn from the data in the table:
[0142] 1. If the colloid structure uses SCA glue of equal thickness, the light distortion value of the information collection area 301 of the window glass 300 is greater than 150mdpt, which does not meet the use requirements of the optical sensor assembly 100 for the window glass 300; and the bonding strength between the anti-reflection film 320 and the laminated glass 310 does not meet the requirements.
[0143] 2. When D1 / W1 is less than 0.18, such as when D1 / W1 is 0.1 and 0.15 respectively, the optical distortion value of the information collection area 301 of the vehicle window glass 300 is greater than 150mdpt, which does not meet the use requirements of the optical sensor assembly 100 for the vehicle window glass 300; and the bonding strength between the anti-reflection film 320 and the laminated glass 310 does not meet the requirements.
[0144] 3. When D1 / W1 is greater than 0.27, such as when D1 / W1 is 0.3, although the bonding strength between the anti-reflection film 320 and the laminated glass 310 meets the requirements, the light distortion value of the information collection area 301 of the vehicle window glass 300 is greater than 150mdpt, which does not meet the use requirements of the optical sensor assembly 100 for the vehicle window glass 300.
[0145] 4. When D1 / W1 is between 0.18 and 0.27, the optical distortion value of the information collection area 301 of the vehicle window glass 300 is ≤150mdpt, the optical distortion result meets the use requirements of the optical sensor assembly 100 for the vehicle window glass 300, and the bonding strength between the anti-reflection film 320 and the laminated glass 310 meets the requirements.
[0146] 5. The larger D1 / W1 is, the stronger the bonding strength between the anti-reflection sheet 320 and the laminated glass 310 is. When D1 / W1>0.2, the bonding strength between the anti-reflection sheet 320 and the laminated glass 310 in the embodiments provided in Table 1 meets the requirements.
[0147] 6. Under the same D1 / W1 value, the window glass 300 having a colloidal structure in which the thickness H1 of the middle portion 331 is 120 μm and the thickness H2 of the edge portion 332 is 200 μm, or having a colloidal structure in which the thickness H1 of the middle portion 331 is 160 μm and the thickness H2 of the edge portion 332 is 240 μm, has a lower light distortion value in the information collection area 301 than the window glass 300 having a colloidal structure in which the thickness H1 of the middle portion 331 is 160 μm and the thickness H2 of the edge portion 332 is 200 μm, or having a colloidal structure in which the thickness H1 of the middle portion 331 is 120 μm and the thickness H2 of the edge portion 332 is 240 μm.
[0148] 7. Under the same D1 / W1 value, the adhesive layer 330 formed after curing by the colloidal structure in which the thickness H1 of the middle part 331 is 160μm and the thickness H2 of the edge part 332 is 240μm, and the colloidal structure in which the thickness H1 of the middle part 331 is 160μm and the thickness H2 of the edge part 332 is 200μm, is stronger than the colloidal structure in which the thickness H1 of the middle part 331 is 120μm and the thickness H2 of the edge part 332 is 200μm, and the colloidal structure in which the thickness H1 of the middle part 331 is 120μm and the thickness H2 of the edge part 332 is 240μm.
[0149] 8. In combination with the optical distortion and adhesion of the product, it is preferred that D1 / W1 is between 0.2-0.25 (including the endpoint values 0.2 and 0.25), and the thickness H1 of the middle part 331 is 160μm and the thickness H2 of the edge part 332 is 240μm, or the thickness H1 of the middle part 331 is 160μm and the thickness H2 of the edge part 332 is 200μm.
[0150] In the second possible implementation, please refer to Fig.10 and Fig.11 , Fig.10 It is a schematic structural diagram of an angled cross section of a second possible implementation of the colloidal structure. Fig.11 is a structural schematic diagram of another angle section of the second possible embodiment of the colloid structure. Different from the first possible embodiment, in the direction where the edge of the colloid structure points to the center of the colloid structure, the thickness of the edge portion 332 of the colloid structure gradually decreases, and the thickness of the middle portion 331 also gradually decreases. Exemplarily, the speed at which the thickness of the edge portion 332 decreases can be the same as the speed at which the thickness of the middle portion 331 decreases, and the minimum thickness of the edge portion 332 can be the same as the maximum thickness of the middle portion 331. The first bonding surface 333 of the colloid structure is a plane. The second bonding surface 334 can be a curved surface, and the second bonding surface 334 is recessed from the edge to the middle. Alternatively, the second bonding surface 334 can include multiple planes, and the multiple planes are arranged at an angle with the first bonding surface 333. This method will be described in detail below, but it should be understood that the setting method of the colloid structure is not limited to this.
[0151] It should be noted that the anti-reflection film 320 and the laminated glass 310 in the first embodiment and the second embodiment of the present application adopt the same bonding process.
[0152] Specifically, the colloid structure includes four parts. Each part includes a partial edge part 332 and a partial middle part 331. Each part includes a glass bonding surface facing the laminated glass 310. The glass bonding surfaces of the four parts constitute the second bonding surface 334 of the colloid structure. The glass bonding surface of each part is connected between the edge of the edge part 332 and the center position of the middle part 331 of the colloid structure. And the angle between the glass bonding surface and the reference surface can be between 8°-15° (including the endpoint values 8° and 15°). The reference surface is a plane parallel to the X direction and the Y direction. The four parts are respectively the first part 3331 and the second part 3332 arranged in sequence along the X direction, and the third part 3333 and the fourth part 3334 arranged in sequence along the Y direction.
[0153] The first part 3331 includes a first end 3335 and a second end 3336 which are arranged opposite to each other along the X direction. The first end 3335 is the edge of the colloid structure in the X direction, and the second end 3336 is the center of the colloid structure. The thickness of the first part 3331 decreases from the first end 3335 to the second end 3336. The first part 3331 includes a first surface 3337 and a second surface 3338 which are arranged opposite to each other along the Z direction (the thickness direction of the vehicle window glass 300). The first surface 3337 is a partial surface of the colloid structure facing the laminated glass 310. The second surface 3338 is a partial surface of the colloid structure facing the anti-reflection film 320. The first surface 3337 is a glass bonding surface. The second surface 3338 is parallel to the X direction and the Y direction. The angle α between the first surface 3337 and the second surface 3338 can range from 8° to 15° (including the end values 8° and 15°).
[0154] The second part 3332 includes a third end 3339 and a fourth end 3340 which are arranged opposite to each other in the opposite direction of the X direction. The third end 3339 is the edge of the colloid structure in the X direction, and the fourth end 3340 is the central part of the colloid structure. The thickness of the second part 3332 gradually decreases from the third end 3339 to the fourth end 3340. The second part 3332 includes a third surface 3341 and a fourth surface 3342 which are arranged opposite to each other in the Z direction (the thickness direction of the vehicle window glass 300), and the third surface 3341 is a partial surface of the colloid structure facing the laminated glass 310. The fourth surface 3342 is a partial surface of the colloid structure facing the anti-reflection film 320. The third surface 3341 is a glass bonding surface. The fourth surface 3342 is parallel to the X direction and the Y direction. The angle α between the third surface 3341 and the fourth surface 3342 can range from 8° to 15° (including the end values 8° and 15°).
[0155] The third part 3333 includes a fifth end 3343 and a sixth end 3344 which are arranged oppositely along the Y direction. The fifth end 3343 is the edge of the colloid structure in the Y direction, and the sixth end 3344 is the center of the colloid structure. The thickness of the third part 3333 gradually decreases from the fifth end 3343 to the sixth end 3344. The third part 3333 includes a fifth surface 3345 and a sixth surface 3346 which are arranged oppositely along the Z direction (the thickness direction of the vehicle window glass 300), and the fifth surface is a partial surface of the colloid structure facing the laminated glass 310. The sixth surface 3346 is a partial surface of the colloid structure facing the anti-reflection film 320. The fifth surface 3345 is a glass bonding surface. The sixth surface 3346 is parallel to the X direction and the Y direction.
[0156] The fourth part 3334 includes a seventh end 3347 and an eighth end 3348 which are arranged opposite to each other in the opposite direction of the Y direction. The seventh end 3347 is the edge of the colloid structure in the Y direction, and the eighth end 3348 is the central part of the colloid structure. The thickness of the fourth part 3334 is gradually thinner from the seventh end 3347 to the eighth end 3348. The fourth part 3334 includes a seventh surface 3349 and an eighth surface 3350 which are arranged opposite to each other in the Z direction (the thickness direction of the vehicle window glass 300), and the seventh surface is a partial surface of the colloid structure facing the laminated glass 310. The eighth surface is a partial surface of the colloid structure facing the anti-reflection film 320. The seventh surface 3349 is a glass bonding surface. The eighth surface 3350 is parallel to the X direction and the Y direction. The present application also provides four embodiment groups and four comparative example groups, wherein the four embodiment groups are the fifth embodiment group, the sixth embodiment group, the seventh embodiment group and the eighth embodiment group. The angle α between the two surfaces of the first part 3331 and the second part 3332 of the colloid structure of the vehicle window glass 300 in the four embodiment groups that are arranged opposite to each other in the Z direction is in the range of 8°-15°. Each embodiment group includes four embodiments, and the ratio of the minimum thickness H3 of the middle part 331 to the maximum thickness H4 of the edge part 332 of each embodiment is different. The four comparative example groups are the fifth comparative example group, the sixth comparative example group, the seventh comparative example group and the eighth comparative example group. Among the four comparative example groups, the thickness of the colloid structure of one comparative example group is uniformly set, and the comparative example group includes four comparative examples, and the thickness of the colloid structure of each comparative example is different; the other three comparative example groups also include four comparative examples, and the ratio of the minimum thickness H3 of the middle part 331 to the maximum thickness H4 of the edge part 332 of each comparative example is different.
[0157] Specifically, the angle α between the two surfaces of the first portion 3331 and the second portion 3332 of the window glass 300 of the fifth embodiment group which are arranged opposite to each other in the Z direction is 8°. The fifth embodiment group includes four embodiments, namely, Embodiment 17, Embodiment 18, Embodiment 19 and Embodiment 20.
[0158] The minimum thickness H3 of the middle portion 331 of Example 17 is 120 μm, and the maximum thickness H4 of the edge portion 332 of the colloid structure is 200 μm.
[0159] The minimum thickness H3 of the middle portion 331 of Example 18 is 120 μm, and the maximum thickness H4 of the edge portion 332 of the colloid structure is 240 μm.
[0160] The minimum thickness H3 of the middle portion 331 of Example 19 is 160 μm, and the maximum thickness H4 of the edge portion 332 of the colloid structure is 200 μm.
[0161] The minimum thickness H3 of the middle portion 331 of Example 20 is 160 μm, and the maximum thickness H4 of the edge portion 332 of the colloid structure is 240 μm.
[0162] The angle α between the two surfaces of the first part 3331 and the second part 3332 of the window glass 300 of the sixth embodiment group which are arranged opposite to each other in the Z direction is 10°. The sixth embodiment group includes four embodiments, namely, Embodiment 21, Embodiment 22, Embodiment 23 and Embodiment 24.
[0163] The minimum thickness H3 of the middle portion 331 of Example 21 is 120 μm, and the maximum thickness H4 of the edge portion 332 of the colloid structure is 200 μm.
[0164] The minimum thickness H3 of the middle portion 331 of Example 22 is 120 μm, and the maximum thickness H4 of the edge portion 332 of the colloid structure is 240 μm.
[0165] The minimum thickness H3 of the middle portion 331 of Example 23 is 160 μm, and the maximum thickness H4 of the edge portion 332 of the colloid structure is 200 μm.
[0166] The minimum thickness H3 of the middle portion 331 of Example 24 is 160 μm, and the maximum thickness H4 of the edge portion 332 of the colloid structure is 240 μm.
[0167] The angle α between the two surfaces of the first portion 3331 and the second portion 3332 of the window glass 300 of the seventh embodiment group which are arranged opposite to each other in the Z direction is 12°. The seventh embodiment group includes four embodiments, namely, Embodiment 25, Embodiment 26, Embodiment 27 and Embodiment 28.
[0168] The minimum thickness H3 of the middle portion 331 of Example 25 is 120 μm, and the maximum thickness H4 of the edge portion 332 of the colloid structure is 200 μm.
[0169] The minimum thickness H3 of the middle portion 331 of Example 26 is 120 μm, and the maximum thickness H4 of the edge portion 332 of the colloid structure is 240 μm.
[0170] The minimum thickness H3 of the middle portion 331 of Example 27 is 160 μm, and the maximum thickness H4 of the edge portion 332 of the colloid structure is 200 μm.
[0171] The minimum thickness H3 of the middle portion 331 of Example 28 is 160 μm, and the maximum thickness H4 of the edge portion 332 of the colloid structure is 240 μm.
[0172] The angle α between the two surfaces of the first part 3331 and the second part 3332 of the window glass 300 of the eighth embodiment group which are arranged opposite to each other in the Z direction is 15°. The eighth embodiment group includes four embodiments, namely, embodiment 29, embodiment 30, embodiment 31 and embodiment 32.
[0173] The minimum thickness H3 of the middle portion 331 of Example 29 is 120 μm, and the maximum thickness H4 of the edge portion 332 of the colloid structure is 200 μm.
[0174] The minimum thickness H3 of the middle portion 331 of Example 30 is 120 μm, and the maximum thickness H4 of the edge portion 332 of the colloid structure is 240 μm.
[0175] The minimum thickness H3 of the middle portion 331 of Example 31 is 160 μm, and the maximum thickness H4 of the edge portion 332 of the colloid structure is 200 μm.
[0176] The minimum thickness H3 of the middle portion 331 of Example 32 is 160 μm, and the maximum thickness H4 of the edge portion 332 of the colloid structure is 240 μm.
[0177] Specifically, the angle α between the two surfaces of the first portion 3331 and the second portion 3332 of the window glass 300 of the fifth comparative example group in the Z direction is 3°. The fifth comparative example group includes four comparative examples, namely, comparative example 17, comparative example 18, comparative example 19 and comparative example 20.
[0178] The thickness H3 of the minimum thickness of the middle portion 331 of Comparative Example 17 was 120 μm, and the maximum thickness H4 of the edge portion 332 of the colloid structure was 200 μm.
[0179] The thickness H3 of the minimum thickness of the middle portion 331 of Comparative Example 18 was 120 μm, and the maximum thickness H4 of the edge portion 332 of the colloid structure was 240 μm.
[0180] The thickness H3 of the minimum thickness of the middle portion 331 of Comparative Example 19 was 160 μm, and the maximum thickness H4 of the edge portion 332 of the colloid structure was 200 μm.
[0181] The thickness H3 of the minimum thickness of the middle portion 331 of Comparative Example 20 is 160 μm, and the maximum thickness H4 of the edge portion 332 of the colloid structure is 240 μm.
[0182] The angle α between the two surfaces of the first portion 3331 and the second portion 3332 of the window glass 300 of the sixth comparative example group which are arranged opposite to each other in the Z direction is 5°. The sixth comparative example group includes four comparative examples, namely, comparative example 21, comparative example 22, comparative example 23 and comparative example 24.
[0183] The thickness H3 of the minimum thickness of the middle portion 331 of Comparative Example 21 was 120 μm, and the maximum thickness H4 of the edge portion 332 of the colloid structure was 200 μm.
[0184] The thickness H3 of the minimum thickness of the middle portion 331 of Comparative Example 22 was 120 μm, and the maximum thickness H4 of the edge portion 332 of the colloid structure was 240 μm.
[0185] The thickness H3 of the minimum thickness of the middle portion 331 of Comparative Example 23 is 160 μm, and the maximum thickness H4 of the edge portion 332 of the colloid structure is 200 μm.
[0186] The thickness H3 of the minimum thickness of the middle portion 331 of Comparative Example 24 is 160 μm, and the maximum thickness H4 of the edge portion 332 of the colloid structure is 240 μm.
[0187] The angle α between the two surfaces of the first portion 3331 and the second portion 3332 of the window glass 300 of the seventh comparative example group which are arranged opposite to each other in the Z direction is 20°. The seventh comparative example group includes four comparative examples, namely, comparative example 25, comparative example 26, comparative example 27 and comparative example 28.
[0188] The thickness H3 of the minimum thickness of the middle portion 331 of Comparative Example 25 was 120 μm, and the maximum thickness H4 of the edge portion 332 of the colloid structure was 200 μm.
[0189] The thickness H3 of the minimum thickness of the middle portion 331 of Comparative Example 26 was 120 μm, and the maximum thickness H4 of the edge portion 332 of the colloid structure was 240 μm.
[0190] The thickness H3 of the minimum thickness of the middle portion 331 of Comparative Example 27 was 160 μm, and the maximum thickness H4 of the edge portion 332 of the colloid structure was 200 μm.
[0191] The thickness H3 of the minimum thickness of the middle portion 331 of Comparative Example 28 was 160 μm, and the maximum thickness H4 of the edge portion 332 of the colloid structure was 240 μm.
[0192] The thickness of the colloid structure of the eighth comparative example group is uniformly set, and the eighth comparative example group includes four comparative examples, namely comparative example 29, comparative example 30, comparative example 31 and comparative example 32. Among them, the thickness of the adhesive layer formed after the colloid structure of comparative example 29 is cured is 120 μm. The thickness of the adhesive layer formed after the colloid structure of comparative example 30 is cured is 160 μm. The thickness of the adhesive layer formed after the colloid structure of comparative example 31 is cured is 200 μm. The thickness of the adhesive layer formed after the colloid structure of comparative example 32 is cured is 240 μm.
[0193] The test results of the vehicle window glass 300 provided by the four embodiment groups and the four comparative example groups are shown in Table 2.
[0194] Table 2, test results of multiple examples and multiple comparative examples of the second possible implementation of the colloidal structure
[0195]
[0196]
[0197] The following conclusions can be drawn from the data in the table:
[0198] 1. If the colloid structure uses SCA optical glue of equal thickness, the light distortion value of the information collection area 301 of the window glass 300 is greater than 150mdpt, which does not meet the use requirements of the optical sensor assembly 100 for the window glass 300; and the bonding strength between the anti-reflection film 320 and the laminated glass 310 does not meet the requirements.
[0199] 2. When the angle α is less than 8°, such as when the angle α is 3° or 5° respectively, although the bonding strength between the anti-reflection film 320 and the laminated glass 310 meets the requirements, the light distortion value of the information collection area 301 of the vehicle window glass 300 is greater than 150mdpt, which does not meet the use requirements of the optical sensor assembly 100 for the vehicle window glass 300.
[0200] 3. When the angle α is greater than 15°, such as when the angle α is 20°, the light distortion value of the information collection area 301 of the vehicle window glass 300 is greater than 150mdpt, and the bonding strength between the anti-reflection film 320 and the laminated glass 310 does not meet the requirements, and therefore the use requirements of the optical sensor assembly 100 for the vehicle window glass 300 are not met.
[0201] 4. In multiple embodiments, when the maximum thickness of the edge portion 332 and the minimum thickness of the middle portion 331 of the colloid structure are the same, the larger the angle α is, the weaker the bonding strength between the anti-reflection film 320 and the laminated glass 310 is. However, when the angle α is in the range of 8°-15°, the light distortion value of the information collection area 301 of the vehicle window glass 300 is small, which is less than or equal to 150mdpt, satisfying the use requirements of the optical sensor assembly 100 for the vehicle window glass 300, and the bonding strength between the anti-reflection film 320 and the laminated glass 310 meets the requirements.
[0202] 4. When the angle α is constant, the greater the minimum thickness of the middle portion 331 of the colloid structure, the better the bonding strength between the anti-reflection sheet 320 and the laminated glass 310 .
[0203] 5. The optical distortion value mainly depends on the angle α. When the angle α is the same, the thicker the maximum thickness of the edge portion 332 and the minimum thickness of the middle portion 331 of the colloid structure, the smaller the optical distortion value of the information collection area 301 of the vehicle window glass 300.
[0204] 6. According to the test results of the above embodiments, when the angle α is between 8° and 15°, the preferred embodiments are Embodiment 19, Embodiment 20, Embodiment 26, Embodiment 27 and Embodiment 28. The preferred embodiments have better results in light distortion test and adhesion test.
[0205] The embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method and core idea of the present application. At the same time, for general technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A colloidal structure, characterized in that: The material of the colloid structure is SCA glue, and the colloid structure includes a middle part and an edge part, the edge part is connected to the periphery of the middle part, and the thickness of the edge part is greater than the thickness of the middle part; The edge portion includes a first sub-portion, which is located on a side of the middle portion facing the first direction, and the width of the first sub-portion in the first direction is a first width. The middle portion includes a first edge and a second edge that are relatively arranged in the first direction, and the distance between the midpoints of the first edge and the second edge is a second width. The ratio of the first width to the second width is between 0.18 and 0.27, wherein the first direction is the width direction of the colloidal structure.
2. The colloid structure according to claim 1, characterized in that The thickness of the edge portion is uniformly set, and the thickness of the middle portion is uniformly set.
3. The colloid structure according to claim 2, characterized in that The thickness of the edge portion is between 160 μm and 260 μm, and the thickness of the middle portion is between 120 μm and 200 μm.
4. The colloid structure according to claim 2, characterized in that The ratio of the thickness of the middle portion to the thickness of the edge portion is between 0.5 and 0.
9.
5. The colloid structure according to claim 2, characterized in that: The edge portion further includes a second sub-portion, which is arranged opposite to the first sub-portion along a first direction, the first sub-portion and the second sub-portion are respectively located on opposite sides of the middle portion, and the width of the second sub-portion in the first direction is the first width.
6. A colloidal structure, characterized in that The material of the colloid structure is SCA glue, the colloid structure includes a middle part and an edge part, the edge part is connected to the periphery of the middle part, the thickness of the edge part is greater than the thickness of the middle part, the edge of the colloid structure points to the center of the colloid structure, the thickness of the edge part gradually decreases, and the thickness of the middle part gradually decreases; The colloid structure includes a glass bonding surface, which is used to connect to the laminated glass. The glass bonding surface is connected between the edge of the edge part and the center position of the middle part. The angle between the glass bonding surface and the reference surface is between 8° and 15°. The reference surface is parallel to the first direction and the second direction. The second direction is the length direction of the colloid structure.
7. The colloid structure according to claim 6, characterized in that The maximum thickness of the edge portion is between 180 μm and 260 μm, and the minimum thickness of the middle portion is between 100 μm and 180 μm.
8. The colloid structure according to claim 6, characterized in that The ratio of the maximum thickness of the edge portion to the minimum thickness of the middle portion is between 0.4 and 0.
7.
9. A vehicle window glass, characterized in that: The laminated glass comprises an outer glass plate, an intermediate layer and an inner glass plate, wherein the intermediate layer is sandwiched between the outer glass plate and the inner glass plate, the outer glass plate has a first surface and a second surface opposite to each other, the second surface faces the intermediate layer, and the inner glass plate has a third surface and a fourth surface opposite to each other, the third surface faces the intermediate layer; An anti-reflection sheet is provided on the fourth surface of the inner glass plate, and along the thickness direction of the laminated glass, the projection of the anti-reflection sheet on the information collection area covers the information collection area, the anti-reflection sheet includes an anti-reflection film and a substrate, the anti-reflection film is provided on the surface of the substrate, and the anti-reflection film is farther away from the laminated glass than the substrate, wherein the anti-reflection sheet is fixed to the fourth surface of the inner glass plate by an adhesive layer, the adhesive layer is made of the colloid structure according to any one of claims 1 to 8, and the thickness of the adhesive layer is uniformly set.
10. The vehicle window glass according to claim 9, characterized in that: The transmittance of the laminated glass to optical signals with a wavelength range of 800nm-1600nm is greater than 88%.
11. The vehicle window glass according to claim 9, characterized in that: The transmittance of the adhesive layer to light with a wavelength of 800nm-1600nm is greater than or equal to 98%.
12. The vehicle window glass according to claim 9, characterized in that: The refractive index of the adhesive layer to light with a wavelength of 800nm-1600nm is in the range of 1.46-1.
49.
13. The vehicle window glass according to claim 9, characterized in that: The substrate includes a peripheral side surface, and a connecting surface and a coating surface that are relatively arranged. The connecting surface is connected to the fourth surface of the inner glass plate through the adhesive layer, and the coating surface is connected to the anti-reflection film. The peripheral side surface is arranged around the connecting surface and the coating surface, and the angle between the connecting surface and the peripheral side surface is 90°.
14. The vehicle window glass according to claim 9, characterized in that: Measured from one side of the first surface, the a value of the Lab value of the visible light reflection color of the information collection area ranges from -3 to +3, and the b value ranges from -3 to +3.
15. A vehicle, characterized in that: It comprises an optical sensor assembly, a vehicle body and a vehicle window glass as described in any one of claims 9 to 14, wherein the vehicle window glass is connected to the vehicle body, the optical sensor assembly is connected inside the vehicle body, and the optical signal of the optical sensor can pass through the vehicle window glass.
Citation Information
Patent Citations
Vehicle window glass and vehicle
CN115139593A
Glass laminate
JP2019172512A